Appraisal of Different Inorganic Inhibitors Action on the Corrosion Control Mechanism of Mild Steel in HNO3 Solution - Magrati, Prakash; Subedi, Dhruba Babu; Pokharel, Durga Bhakta; Bhattarai, Jagadeesh (Journal of Nepal Chemical Society, 2020)
Effects of eco-friendly inorganic inhibitors (i.e., calcium nitrate, zinc sulfate, sodium hexametaphosphate and sodium tetra-borate or borax) for the mild steel corrosion control in 1 M HNO3 solution open to air at 28±1 °C were studied using corrosion, inhibition efficiency, and corrosion potential tests. The corrosion rate of the mild steel is increased with increasing the concentrations of HNO3 solution from 0.01 M to 1 M. The uses of 200-2400 ppm of these inhibitors enhanced the corrosion resistance properties of the mild steel in 1 M HNO3 solution. The corrosion resistance property of the mild steel is generally decreased with increasing the concentration of all corrosion inhibitors used here. The most efficient corrosion inhibitor is found to be calcium nitrate and it is followed by zinc sulfate, sodium hexametaphosphate, and borax subsequently. Adsorption of these inorganic salts inhibitors on the mild steel surface obeyed Langmuir adsorption isotherm. Consequently, the corrosion inhibition mechanism of the four inorganic salts for the mild steel corrosion control can be explained based on the formation of the passive film. It is found from the corrosion potential measurement that the cathodic type of corrosion inhibition action was by calcium nitrate, whereas zinc sulfate, sodium hexametaphosphate, and borax are acted as a mixed type of the inhibitors in 1 M HNO3 solution. In summary, all four inorganic inhibitors utilized in the present study can be applied as an environmentally friendly inhibitor to control the corrosion of the mild steel in aggressive HNO3 solutions.